Cover Image. Issue 6 (21st October 2021) - Green, Helen; Gleadow, Andrew; Finch, Damien; Myers, Cecilia; McGovern, Jenna
Abstract : Cover : The cover image is based on the Research Article Micro‐stromatolitic laminations and the origins of engraved, oxalate‐rich accretions from Australian rock art shelters by Helen Green et al., https://doi.org/10.1002/gea.21882 .